Current use, training, and barriers in point‐of‐care ultrasound in hospital medicine: A national survey of VA hospitals. Issue 8 (17th July 2022) - Williams, Jason P.; Nathanson, Robert; LoPresti, Charles M.; Mader, Michael J.; Haro, Elizabeth K.; Drum, Brandy; O'Brien, Edward; Khosla, Rahul; Boyd, Jeremy S.; Bales, Brian; Wetherbee, Erin; Sauthoff, Harald; et al.
Abstract: Background: Point‐of‐care ultrasound (POCUS) can reduce procedural complications and improve the diagnostic accuracy of hospitalists. Currently, it is unknown how many practicing hospitalists use POCUS, which applications are used most often, and what barriers to POCUS use exist. Objective: This study aimed to characterize current POCUS use, training needs, and barriers to use among hospital medicine groups (HMGs). Design, Setting, and Participants: A prospective observational study of all Veterans Affairs (VA) medical centers was conducted between August 2019 and March 2020 using a web‐based survey sent to all chiefs of HMGs. These data were compared to a similar survey conducted in 2015. Result: Chiefs from 117 HMGs were surveyed, with a 90% response rate. There was ongoing POCUS use in 64% of HMGs. From 2015 to 2020, procedural POCUS use decreased by 19%, but diagnostic POCUS use increased for cardiac (8%), pulmonary (7%), and abdominal (8%) applications. The most common barrier to POCUS use was lack of training (89%), and only 34% of HMGs had access to POCUS training. Access to ultrasound equipment was the least common barrier (57%). The proportion of HMGs with ≥1 ultrasound machine increased from 29% to 71% from 2015 to 2020. An average of 3.6 ultrasound devices per HMG was available, and 45% were handheld devices. Conclusion: From 2015 to 2020, diagnostic POCUS use increased, while procedural use decreased among hospitalists in the VA system. Lack of POCUS training is currently the most common barrier to POCUS use among hospitalists.